Protein context shapes the specificity of SH3 domain-mediated interactions in vivo - Ugo Dionne (Nature Portfolio, 2021)
The SRC Homology 3 (SH3) domains mediate protein–protein interactions (PPIs). Here, the authors assess the SH3-mediated PPIs in yeast, and show that the identity of the protein itself and the position of the SH3 both affect the interaction specificity and thus the PPI-dependent cellular functions.